Estudo e análise dos cargos de liderança na TI do Rio Grande do Sul: o caso dos Chief Information Officer - Ghisio, Evans (Universidade do Vale do Rio dos Sinos, 2010)
With the advent of information technology was the need for human resources able to handle the same, since the first professionals engaged in Information Technology stemmed from physics, mathematics and engineering. Already in the mid-60th century XX, the technical professionals working in data processing with information primarily collected from computer languages and provided numerical data and tabulated. Then there's a racing in both the operational and in need of professionals engaged in technology. This paper seeks to specifically determine the trajectory of the leadership positions and watch your near future, their tasks and requirements for highly productive and efficient management of information technology in any business or organization.
Keywords: Tecnologia da iInformação; Recursos humanos; Profissionais técnicos; Liderança em TI; Gestão eficiente; Information technology; Human resources; Technical professionals